Survival in Papillary Thyroid Microcarcinoma: A Comparative Analysis Between the 7th and 8th Versions of the AJCC/UICC Staging System Based on the SEER Database - Yang, Fan; Zhong, Qi; Huang, Zhigang; Lian, Meng; Fang, Jugao (Frontiers in Endocrinology, 2019)
Background: Considerable modifications have been introduced in the new edition of the American Joint Committee on Cancer/Union for International Cancer Control (AJCC/UICC) TNM staging system. Based on the National Cancer Institute’s Surveillance, Epidemiology, and End Results (SEER) database, this study aimed to compare the 7th and 8th editions of the AJCC/UICC TNM staging system for patients with papillary thyroid microcarcinoma (PTMC) and follicular variant papillary thyroid microcarcinoma (FVPTMC). Methods: A Data from 2004 to 2014 of 39,032 patients registered in the SEER database were included. The 7th and 8th editions of the AJCC/UICC staging system were compared in terms of TNM staging, age cutoff, and clinical staging. Patient survival was evaluated using Kaplan‐Meier and multivariable Cox proportional hazards models. The American Thyroid Association (ATA) risk stratification system was integrated with the AJCC/UICC staging system for further investigation. Receiver operating characteristic (ROC) curves, Harrell’s C‐index, Akaike information criterion (AIC), and the Bayesian information criterion (BIC) were used to assess the models’ performances. Results: Revised TNM categories, age cutoff, and clinical staging in the 8th edition resulted in reclassification of the overall stage. Applying the 8th edition, 1,278 stage III and 425 stage IV patients were reclassified as stage I; 950 stage III and 459 stage IV patients were reclassified as stage II; 77 stage IV patients were reclassified as stage III; and only 88 patients remained in stage IV. All patients in stage I, according to the 7th edition, remained in this stage when using the 8th edition. Patients classified into higher stages (III and IV) in the 8th edition showed a worse prognosis than those classified into same stages in the 7th edition. The 8th edition proved to be a better model with higher prognostic efficacy survival (higher AUC and C-index, lower AIC and BIC) than the 7th edition. When integrated with the ATA risk stratification system, the 8th edition still showed better discriminative power for patients in the higher risk group. Conclusion: Based on the SEER database, the 8th edition of the AJCC/UICC staging system has better prognostic efficacy than the 7th edition for patients with PTMC and FVPTMC.